Ergonomic Analysis of Functional Endoscopic Sinus Surgery Using Novel Inertial Sensors. (6th August 2021) - Arrighi‐Allisan, Annie E.; Garvey, Katherine L.; Wong, Anni; Filip, Peter; Shah, Janki; Spock, Todd; Del Signore, Anthony; Cosetti, Maura K.; Govindaraj, Satish; Iloreta, Alfred Marc
Abstract : Objectives/Hypothesis: Suboptimal ergonomics during endoscopic sinus surgery can lead to considerable physical discomfort and fatigue for the surgeon. The purpose of this pilot study is to objectively evaluate the ergonomic positions of trainee and attending surgeons while performing functional endoscopic sinus surgery (FESS). Study Design: Pilot prospective trial. Methods: Six surgeons (two attendings and four trainees) performed FESS while wearing 11 inertial measurement units (IMUs) affixed to either side of each major joint. Screen placement was standardized to be 1 m directly in front of the surgeon and on the patient's left, 0–15° declined from the surgeons' eyes. Bed height was standardized such that the workspace was 0 to 10 cm below the elbows. IMU data were analyzed to calculate joint angles. Ideal joint angles (i.e., <10° for neck and trunk) were determined by the validated Rapid Entire Body Assessment tool. Subjects subsequently completed a modified National Aeronautics and Space Administration Task Load Index to assess cognitive and physical burden and pain. Student's t ‐test was employed to detect differences between groups. Results: Trainees adopted positions involving significantly greater neck flexion (9.90° vs. −6.48°, P  = .03) and reported significantly higher frustration levels (3.04 vs. 1.33, P  = .02) while operating than attendings. For both cohorts, increased operative time was significantly correlated with greater back flexion ( r  = 0.90, P  = .02; r  = 0.55, P  = .04, respectively). Conclusions: Our data suggest that trainees operate with higher risk neck postures than do attendings. These data indicate high‐risk operative postures may be borne of inexperience and present an opportunity for postural interventions at an early stage of training. Level of Evidence: NA Laryngoscope, 132:1153–1159, 2022